2014
DOI: 10.1016/j.chembiol.2014.07.023
|View full text |Cite
|
Sign up to set email alerts
|

A Divalent Metal Ion-Dependent N 1 -Methyl Transfer to G37-tRNA

Abstract: The catalytic mechanism of the majority of S-adenosyl methionine (AdoMet)-dependent methyl transferases requires no divalent metal ions. Here we report that methyl transfer from AdoMet to N1 of G37-tRNA, catalyzed by the bacterial TrmD enzyme, is strongly dependent on divalent metal ions and that Mg2+ is the most physiologically relevant. Kinetic isotope analysis, metal rescue, and spectroscopic measurements indicate that Mg2+ is not involved in substrate binding, but in promoting methyl transfer. Based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

6
2

Authors

Journals

citations
Cited by 26 publications
(80 citation statements)
references
References 50 publications
6
74
0
Order By: Relevance
“…At high intracellular [Mg 2+ ], translation of mgtL is rapid and complete (inset 2b), facilitating stem loop B formation, which exposes the rut site and leads to Rho binding and transcription termination, turning mgtA OFF (inset 3b). EF-P, which assists the incorporation of Pro residues into nascent proteins (16) and TrmD, which catalyzes Mg 2+ -dependent m 1 G37 methylation of all three tRNA Pro species (26), are required for rapid translation of mgtL (inset 4). Nucleotide changes in red denote mutations that repress mgtA expression, and nucleotide changes in green denote mutations that turn on mgtA expression.…”
Section: A Mutationmentioning
confidence: 99%
See 1 more Smart Citation
“…At high intracellular [Mg 2+ ], translation of mgtL is rapid and complete (inset 2b), facilitating stem loop B formation, which exposes the rut site and leads to Rho binding and transcription termination, turning mgtA OFF (inset 3b). EF-P, which assists the incorporation of Pro residues into nascent proteins (16) and TrmD, which catalyzes Mg 2+ -dependent m 1 G37 methylation of all three tRNA Pro species (26), are required for rapid translation of mgtL (inset 4). Nucleotide changes in red denote mutations that repress mgtA expression, and nucleotide changes in green denote mutations that turn on mgtA expression.…”
Section: A Mutationmentioning
confidence: 99%
“…Without this methylation, translation of Pro codons is prone to +1-frameshifting (25). TrmD is unique among AdoMet-dependent nucleic acid methyltransferases in that it requires Mg 2+ for its activity (26). TrmD is essential for viability, but the heat-sensitive trmD27 (S88L) allele (27) enabled us to test whether reduction in the levels of m 1 G37-tRNA Pro would decrease the efficiency of translation of the Pro codons of mgtL.…”
Section: A Mutationmentioning
confidence: 99%
“…[40][41][42][43][44][45][46][47] The transcript of human mttRNA Leu (UUR) was used as the substrate for the synthesis of m 1 G9. The radioactive methyl donor was purchased from Perkin-Elmer.…”
Section: Enzyme Activity Assaysmentioning
confidence: 99%
“…In the resultant intermediate state, the developing negative charge on O 6 of G37 is stabilized by the positively charged guanidine group of the strictly conserved Arg154*. In a recent study, a Mg 2+ ion was found to stabilize the developing negative charge on O 6 of G37 after proton abstraction, thus contributing to the catalytic mechanism of methyl transfer (19). In the mF o -DF c map of the tRNA•sinefungin-bound form, a weak electron density was identified near N 7 of G37, which might be a partially bound Mg 2+ ion (Fig.…”
Section: Significancementioning
confidence: 99%